Dynasties and the Political Budget Cycle - Gianmarco Daniele; Paul Vertier (Center for Economic Studies and ifo Institute (CESifo), 2016)
Families often play a significant role in representative democracies. In this paper, we test the extent to which dynastic and non-dynastic leaders differ in their policy making. Our empirical analysis focuses on local politics in Italy, using a large sample of mayors and mayoral candidates in the period 1985–2012. We highlight that dynastic candidates have more successful political careers and that power is self-perpetuating, as those in power are more likely to establish a dynasty. We then test whether dynastic mayors enforce different policies than their non-dynastic counterparts. We find no effect on average spending, revenues or transfers. Conversely, we show that dynastic mayors increase spending and obtain higher transfers during the year prior to an election, especially when they are eligible to run for re-election. We discuss mechanisms that might explain this strategic behavior.
Keywords: H11; 330; dynasties; political budget cycles